(untitled) (Academia Science Repository, 2023)
The article describes detail processing experiments with a circular body shape and effective methods are mentioned. Practical skills in working with processing machines are described on the outer cylindrical surfaces of the details. Currently, the requirements for processing accuracy have increased significantly, which is due to the special requirements of product exploitation. The purpose of this work is to explore effective ways to control accuracy.